(untitled) (Fiep Bulletin - online, 2011)
Diabetes mellitus is a metabolic disorder caused by the secretion and / or action of insulin, hyperglycemia and / or hyperinsulinemia, that can influence the healing of injuries. So is necessary a holistic view of the factors which affect the healing process, such as control of underlying pathology (hypertension, diabetes mellitus), nutritional, infectious, drug, and especially the treatment and prevention of new lesions. The objective of this review article is to characterize the scientific production published in the Virtual Health Library (VHL), the influence of diabetes mellitus on wound healing, as the author of the research, year of publication, the authors category, type of study and approach the subject matter related, the paper published and local search. The research is a descriptive (literature review) and quantitative approach, carried out in VHL (LILACS, MEDLINE, SciELO and BDENF and BBO), using the key words "diabetes mellitus" and "healing". During the collection, there were 6 items: 1 LILACS, 3 MEDLINE, 1 in SCIELO and 1 in the BBO. The data collected were sketched on a framework for better visualization and understanding. According to the survey, most studies were located in MEDLINE (50.0%) in the year 2008 (50.0%), produced by teachers graduate (100.0%), using the study descriptive (50.0%) and a quantitative approach (83.3%). The subjects discussed were the treatment of ulcers in patients with diabetes (66.7%) and the influential factors for wound healing (33.3%), among them diabetes mellitus. On the place of publication, 50.0% were state of Sao Paulo and 50.0% international. Diabetes is an important risk factor for the development of lesions and influence in the healing process, aggravating the condition of the patient and contributing to the chronicity of these wounds, changing patterns of morbidity in these individuals.